Optimization of Additives Concentration in Polymeric Membrane Fabrication (Low Polymer Concentration) - Cheah, Choon Hen (2015)
Recent developments in technology have resulted in breakthroughs in wastewater treatment and reclamation for water reuse. Membranes technology may be an option when they enable the removal of contaminants. In this study, the potential of powdered activated carbon (PAC) as an additive in polyethersulfone (PES) membrane fabrication to improve the performances of membrane was determined. Three membranes with different additive concentrations (0 wt. %, 5 wt. %, and 11 wt. %) were tested to find out the flux produced and rejection to salt water by each membrane. The results obtained showed that the membrane with 11 wt. % of PAC produced the most flux than others. Flux produced was in the range between 5.146 × 10-5 m3 /m2 /s and 6.549 × 10-5 m3 /m2 /s. Besides, membrane with 11 wt. % of additives also had the highest rejection for salt water, which reject 76% and 79%. Apart from that, morphology of membrane with and without additive was studied using Scanning Electron Microscopy (SEM). Structure of membrane has been shown that membrane with PAC was having more macro voids formation than without PAC. Furthermore, tensile testing for the membranes was also studied. The ultimate tensile strength (UTS) of the membrane without PAC showed a higher readings which was 2.261 MPa. Meanwhile, membrane with 5 wt. % have lower UTS compare to 0 wt. %. Yet, the UTS was increase as there is more PAC was added into the membrane as shown in membrane with 11 wt. %.